Biomarkers Used for the Diagnosis of Diseases - Nimse, Satish Balasaheb; Park, Min (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The detection and quantification of with high precision nucleic acid biomarkers and protein biomarkers in resource-limited settings is key to the early diagnosis of diseases and for monitoring the effects of treatments. As there is an enormous demand for high-quality biomarker detection platforms that are robust and highly applicable in resource-limited settings, this book is devoted to exploring methods for detection and quantification of biomarkers, focusing on the recent advances in this field.